Economic justification for mushroom cultivation - Sergeyeva Natalya; Vasilchenko Tatiana (E3S Web of Conferences, 2024)
The article presents the economic justification for cultivating two mushroom varieties: OUSTER type Oyster Mushroom and Flammulina velutipes Velvet Shank Mushroom over a period of three years. The process equipment list and the cost of the equipment are provided. The project implementation would require greenhouses with the area of about 300 square metres, one-off capital investments of about 7 million roubles. Detailed estimation of annual current costs is presented and the cost of production is evaluated. The expected production profitability during the first year of the project implementation is 16.5%, in the second year it is 23.2%, and it is more than 27% in the third year. The project would propose a feasible solution for both medium and small agrarian businesses.The issue of obtaining readily available (or so called fast) protein for complete human nutrition is of global concern. Producing animal protein requires a long time for rearing; poultry protein production takes a little less, a few months; to obtain protein from mushrooms one month is enough. Mushroom cultivation could be a solution to the global challenge of ensuring world food security, in line with the UN Sustainable Development Goal to end hunger. On the other hand, changing market needs for food, sanction embargo and the tasks of the government import substitution programme in Russia stresses the need for developing domestic production.